Prospects of expenditure on security and defense (2017)
Colombia has been a fighting country in search of peace, since many years ago it has had to negotiate in different ways and using different strategies seeking to eliminate the conflict. In this essay will be released information on the post-agreement in Colombia a brief account of the different periods of the armed conflict that has been presented throughout history in Colombia and its main actors, as reflected on The different negotiations and peace processes that have been developed and the impact of post-agreement on society in terms of the economy, after the Colombian government reached the demobilization of the armed groups, concluding with some reflections on how the Prospects of spending on security and defense of the Armed Forces.